2021
DOI: 10.1136/rapm-2021-102910
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of opioid consumption from day of surgery to 28 days postoperatively: a prospective cohort study in patients undergoing abdominal, joint, or spine surgery

Abstract: IntroductionDescriptions of opioid use trajectories and their association with postsurgical pain and opioid consumption are limited. We hypothesized that trajectories of opioid consumption in the first 28 days following surgery would be associated with unique patterns of pain and duration of opioid use.MethodsA prospective longitudinal cohort of patients undergoing elective inpatient abdominal, joint, or spine surgery between June 2016 and June 2019 was studied. At hospital discharge and every 7 days for 28 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…For patients and clinicians finding opioid dose tapering to be challenging in the setting of preoperative opioid tolerance, consultation with pain medicine, behavioral health, or addiction medicine specialists should be used in lieu of persistent dose escalation and ongoing medication refills. The primary prescriber and surgical care team can collaborate to identify an aberrant trajectory of recovery and medication need 55…”
Section: Discussionmentioning
confidence: 99%
“…For patients and clinicians finding opioid dose tapering to be challenging in the setting of preoperative opioid tolerance, consultation with pain medicine, behavioral health, or addiction medicine specialists should be used in lieu of persistent dose escalation and ongoing medication refills. The primary prescriber and surgical care team can collaborate to identify an aberrant trajectory of recovery and medication need 55…”
Section: Discussionmentioning
confidence: 99%
“…Our parents may have also been overwhelmed with caring for their child after surgery and having their other children at home during the coronavirus disease 2019 pandemic lockdown period and required remote learning. The use of a web-based survey accessible by a smartphone has been shown to produce lower response rates in patients over 75 years of age [ 12 ]. Our participants were all parents of children under 19 with the majority being in their third and fourth decades of life.…”
Section: Discussionmentioning
confidence: 99%
“…Other survey modalities have been associated with improved response rates. In a similar study that surveyed adult opioid use postoperatively after hospital discharge, patients were required to give informed, written consent prior to hospital discharge and were reached by phone calls on a weekly basis for four weeks [ 12 ]. A comparison in response rates reveals dramatically improved results.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective cohort analysis of insurance claims data comprizing over 57 000 patients did not find clinically significant differences in postsurgical opioid utilization in terms of prescriptions filled or dosages in MME/day regardless of whether patients had stable, increasing or decreasing trajectories of presurgical opioid utilization 131. However, numerous studies have found that intraoperative remifentanil use is associated with greater postsurgical opioid requirements and hyperalgesia,130 132 and a recent large prospective cohort study in over 1800 patients found that a stable or increasing trajectory of postsurgical opioid requirements within the first month after joint, spine or abdominal surgery was associated with a significantly greater likelihood of subsequent chronic opioid use (>6 months postsurgery) 133. These trends suggest that the reduction of perioperative opioid exposure and opioid requirements via multimodal analgesic strategies may reduce postsurgical opioid requirements and improve safety.…”
Section: Chronification Of Pain In the Perioperative Settingmentioning
confidence: 99%